Penyuluhan HUkum Dalam Upaya Meningkatkan Kesadaran Hukum Berlalu Lintas Melalui Pemahaman Terhadap Undang-undang Nomor 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan Di SMKN 2 Marabahan Kabupaten Barito Kuala - Fitri, Muhammad Syahrial; Hanafi, Hanafi; Nahdhah, Nahdhah (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2021)
Abstract Road traffic and transportation have a strategic role in supporting national development and integration as part of efforts to advance public welfare as mandated by the 1945 Constitution of the Republic of Indonesia. As part of the national transportation system, road traffic and transportation must be developed in their potential and role for realizing security, welfare, orderliness of traffic and road transportation in the framework of supporting economic development and development of science and technology, regional autonomy, and accountability of state administration. With regard to the issue of public legal awareness related to the importance of safe and orderly traffic for a culture of obeying traffic, especially among students, extension agents will carry out this legal counseling at SMK Negeri 2 Marabahan, Barito Kuala Regency. Observations made by the extension agents were that SMK Negeri 2 Marabahan was located right on the edge of the Trans Kalimantan Km highway. 24 or a road connecting the South Kalimantan region with Central Kalimantan. Most of the students go to school using two-wheeled vehicles (motorbikes) of various types and brands. But the phenomenon of awareness of the law of safe and orderly traffic is very lacking. This can be seen when leaving or coming home from school, it is not uncommon for students to speed, ride more than two people (3 people on a motorcycle), chat while driving simultaneously, use cellphones while driving, vehicles used are not up to standard (modification result) and various types of traffic violations committed. In the observations of the instructor, the above matters are often part of accident cases that often involve school students. Various factors that cause a lack of awareness about driving and traffic in an orderly and safe manner are a lack of understanding and knowledge as well as a lack of socialization or legal counseling to school students, especially in the Anjir Muara and Anjir Pasar areas, Barito Kuala Regency. The purpose of this service is to increase legal awareness and understanding of the students of SMKN 2 Marabahan, Barito Kuala Regency in understanding the importance of orderly and safe traffic in accordance with the legal rules in Law Number 22 of 2009 concerning Road Traffic and Transportation. With the increased awareness and understanding of the law, it can minimize the number of violations and cases of traffic accidents involving school students.